The usage of Human Resources Management Information System (HRMIS) in the Malaysian Armed Forces: Empirical evidence in a military setting / Mohd Azmi Arifin - Mohd Azmi , Arifin (2020)
The use of information and communication technology (ICT) among individuals and organisations is growing in accordance with technology invention, innovation and consumer needs. Like other organisations, the Malaysian Armed Forces (MAF) are not left behind to adopt technology in its management and operations. In the individual context, the use of technology can enhance the performance and quality of MAF’s personnel work. However, the BADSA’s report in 2017 found that the use of HRMIS was not optimal in the MAF. Only 32.4 per cent of the 37 units that were audited had used the system. Therefore, this study aimed to investigate the factors that influence HRMIS use and its impact on MAF personnel. This study chose to use a quantitative method, starting with a preliminary study to identify initial factors that influence HRMIS use. The identified factors then have been integrated with the Information Systems Success Model (ISSM). From this integrated framework, measurement items have been developed by selecting items from previous studies. In addition, some items have been added based on FGDs and interviews results. The finalised items formed a set of questionnaires used in phase 2 of this study and were distributed to 750 HRMIS users in various MAF units. The analysis on the returned questionnaire has yielded findings which are significant factors in influencing the use of HRMIS and impact of HRMIS to MAF personnel. Findings from this study confirmed that factors influencing the use of HRMIS among MAF personnel are information quality, system quality, commander support, technical training, and ICT infrastructure. Based on these factors, this study recommends measures to improve the rate of HRMIS usage among MAF personnel. The study also found a significant positive relationship between HRMIS usage and individual benefits, thus showing the positive impact of HRMIS use on MAF personnel.